The emotional stability development, Ages 11 to 14 Years (Journal Of Educational and Psychological Researches, 2017)
The current research aims to identify 1) the differences of emotional stability development level according to the variable of age; and 2) the differences of emotional stability development level according to the variable of gender (male, female). This study employed a descriptive approach, whereby a total of 165 primary and secondary school student was randomly selected from the directorate of AL -rusafa side (1st rusafa) of Baghdad province to constitute the sample of the study. The questionnaire was created based on the previous testes and studies that are relevant to emotional stability, and all its psychometrics features were examined. The researcher analyzed the data using SPSS statistics. Based on the result of data analysis, the researcher found out that: 1) The emotional stability development depend on the advancement of  age of the current sample; 2) The emotional stability development and its development affect by many factors and variables such as experience and maturity; and 3) There was no significance between male and female at the age of (11) , (14), but there was a significance at the age (12) , (13).